Johan Alamsyah - Johan Alamsyah (Yurisprudentia: Jurnal Hukum Ekonomi, 2015)
Spouse Apostasy after the marriage that resulted not get along among them is the reason for the divorce set out in Article 116 h KHI, so that the provisions of this article need to be analyzed in the perspective of sync in relation to other articles in KHI. The conclusion is based on the analysis of synchronization of the law is that it turns the provisions of Article 116 letter h KHI conflict with other articles of the KHI, ie will divorce, about the notion of apostasy, meaning household harmony, the legitimacy of religious differences in marriage.